Effect of a Clinical Nursing Practice Guideline of Enteral Nutrition Care on the Duration of Mechanical Ventilator for Critically Ill Patients - Apinya Koontalay; Amornrat Sangsaikaew; Arunee Khamrassame (Elsevier, 2020)
Purpose: Early enteral nutrition (EN) can improve clinical outcomes in critically ill patients. This study aimed to evaluate the effects of this clinical nursing practice guideline (CNPG) of EN care on the duration of mechanical ventilator in critically ill patients to investigate whether it was able to improve clinical outcomes. Methods: This study compares a pretest-posttest design for the two groups, which was done before and after to determine the effects of a CNPG of EN care on the duration of a mechanical ventilator in critically ill patients. This study was performed on 44 critically ill patients admitted to the intensive care unit (ICU). The patients were divided into two groups according to EN. For the intervention group, CNPG started within the first 48 hours of admission to the ICU, and for the control group, they received standard nursing care. Results: After the implementation, it showed significant associations between the duration of mechanical ventilator in ICU. The intervention group who received the CNPG had significantly shorter starting time of EN and a reduced duration of mechanical ventilator than those in the control group (p < .001). Conclusion: A CNPG for EN care reduced the duration of mechanical ventilator. This could possibly improve the delivery of target calories when compared with current standard practice and improve the outcome of critically ill patients. Keywords: critical illness, enteral nutrition, practice guideline, ventilators, mechanical